Thiopurine withdrawal during sustained clinical remission in inflammatory bowel disease: relapse and recapture rates, with predictive factors in 237 patients. Issue 11 (6th October 2014) - Kennedy, N. A.; Kalla, R.; Warner, B.; Gambles, C. J.; Musy, R.; Reynolds, S.; Dattani, R.; Nayee, H.; Felwick, R.; Harris, R.; Marriott, S.; Senanayake, S. M.; et al.
Summary Background Thiopurines (azathioprine and mercaptopurine) remain integral to most medical strategies for maintaining remission in Crohn's disease (CD) and ulcerative colitis (UC). Indefinite use of these drugs is tempered by long‐term risks. While clinical relapse is noted frequently following drug withdrawal, there are few published data on predictive factors. Aim To investigate the success of planned thiopurine withdrawal in patients in sustained clinical remission to identify rates and predictors of relapse. Methods This was a multicentre retrospective cohort study from 11 centres across the UK. Patients included had a definitive diagnosis of IBD, continuous thiopurine use ≥3 years and withdrawal when in sustained clinical remission. All patients had a minimum of 12 months follow‐up post drug withdrawal. Primary and secondary end points were relapse at 12 and 24 months respectively. Results 237 patients were included in the study (129 CD; 108 UC). Median duration of thiopurine use prior to withdrawal was 6.0 years (interquartile range 4.4–8.4). At follow‐up, moderate/severe relapse was observed in 23% CD and 12% UC patients at 12 months, 39% CD and 26% UC at 24 months. Relapse rate at 12 months was significantly higher in CD than UC (P = 0.035). Elevated CRP at withdrawal was associated with higher relapse rates at 12 months for CD (P = 0.005), while an elevated white cell count was predictive at 12 months for UC (P = 0.007). Conclusion Thiopurine withdrawal in the context of sustained remission is associated with a 1‐year moderate‐to‐severe relapse rate of 23% in Crohn's disease and 12% in ulcerative colitis.